The study of the qualitative and quantitative composition of the algal flora of lake Balkhash in the areas of bays Bertis and Baytal (Experimental biology, 2015)
The algae species composition of lake Balkhash in the bay Bertis area and Baytal gulf is studied. In water samples collected in the bay Bertis area, in species composition green and blue-green microalgae is dominated, however, the frequency of occurrence is dominated by diatom microalgae. 26 species of microalgae identified. In water samples collected in the bay Baytal area the number of species taxa of microalgae increazed to 38. Among certain species of microalgae is dominated by green, then diatom microalgae. It is established that the number of species of phototrophic microorganisms increases significantly with advancing from the most polluted Bertis gulf to more remote and less susceptible to human impacts Baytal gulf. Based on the definition of the indicator-saprobic species of microalgae assess the environmental situation of the lake. It is established that as reduce pollution and improve water quality there has been a gradual decline saprobity. It is established a moderate contamination by α – mesosaprobic type of water in the bay Bertis area and moderate for β – mesosaprobic type of water in the Baytal gulf.
Keywords: microalgae; cyanobacteria; supranote; algoflora; bioindication